Share

Books Shortlist

# If X =(Sqrt(A + 3b) + Sqrt(A - 3b))/(Sqrt(A + 3b) - Sqrt(A - 3b)) Prove that 3bx^2 - 2ax + 3b = 0 - ICSE Class 10 - Mathematics

#### Question

If x = (sqrt(a + 3b) + sqrt(a - 3b))/(sqrt(a + 3b) - sqrt(a - 3b)) prove that 3bx^2 - 2ax + 3b = 0

#### Solution

Since x/1 = (sqrt(a + 3b) + sqrt(a - 3b))/(sqrt(a + 3b) - sqrt(a - 3b))

Applying componendo and dividendo we get

(x + 1)/(x - 1) = (sqrt(a + 3b) + sqrt(a - 3b) + sqrt(a + 3b) - sqrta - 3b)/(sqrt(a + 3b) + sqrt(a - 3b) - sqrt(a + 3b) + sqrt(a - 3b))

(x + 1)/(x - 1)= (2sqrt(a + 3b))/(2sqrt(a - 3b))

Squaring both sides.

Again applying componendo and dividendo

(x^2 + 2x + 1 + x62 - 2x + 1)/(x^2 + 2x + 1 - x^2 + 2x - 1) = (a + 3b + a - 3b)/(a + 3b - a + 3b)

(2(x^2 + 1))/(2(2x)) = (2(a))/(2(3b))

3b(x^2 + 1) = 2ax

3bx^2 - 2ax + 3b = 0

Is there an error in this question or solution?

#### APPEARS IN

Selina Solution for Selina ICSE Concise Mathematics for Class 10 (2018-2019) (2017 to Current)
Chapter 7: Ratio and Proportion (Including Properties and Uses)
Ex.7C | Q: 12

#### Video TutorialsVIEW ALL [1]

Solution If X =(Sqrt(A + 3b) + Sqrt(A - 3b))/(Sqrt(A + 3b) - Sqrt(A - 3b)) Prove that 3bx^2 - 2ax + 3b = 0 Concept: Proportions.
S